A suburb surrounded by farms with a specific location – environtmental attributes of Kecskemét–Méntelek and the future prospects of the local society - KOVÁCS, András Donát (Discussion Papers, 2011)
Most of our market towns on the Great Hungarian Plain are surrounded by diverse suburban fields, mosaic suburban zones. Individual outskirting processes have been in progress in the area of Kecskemét in the past period; therefore, the suburbs of the traditional market town – primarily due to the different natural characteristics and the structural differential effects in connection with the historical development – have become very varied. During the 20th century economic and social changes cleared a way for a new development – usually different to the ones before – within the borders of Kecskemét. The increasing number of farms from the second half of the 19th century, the suburban settlement centres evolved between the two World Wars, or the double settlements developing in the garden zones have made the suburban areas diverse as well as the villages growing after the Second World War, the suburban yards given away in the borderland or the developing building of suburban houses since the change of regime. In the 20th century, a new type of spatial development was created in the town of Kecskemét by various environmental and socio-economical transformations. Due to this development, the present periphery of the town consists of several units of different features. Méntelek – a remote borough of special conditions – is one of those scattered settlements in the Kecskemét micro-region (even in the Great Plain) where depopulation may be cut and scattered farms may regain popularity. Based on a spatial empirical research, our study aims to show the specific attributes on the urban-rural fringe, and the future of the region. It can be generally said that the rural areas of Hungary are facing complex and very difficult challenges. Unfortunately, many signs show that the disadvantages of rural areas – lagging of economical and social status – have been growing in the past few years. This is the reason why these inner peripheries must be directed to be lined up with more developed areas, otherwise areas in question can lose their population and economical and cultural functions specific to these settlements can also cease. The examined area around Kecskemét has indeed several issues, however we think that there are many future opportunities in the area between the Duna and the Tisza. Our belief is that suburban, farm-like esplanades like Méntelek can play an important role in preserving the specific natural-ecological-cultural attributes of the Hungarian Plain together with the appearance of traditional as well as post-modern values in endurance of the farms or rather reinterpretation of the farm lifestyle.